Power up your to-do list (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. A well-organised to-do list means the tasks with the highest impact get done first. Nothing gets missed, and you end the day with a warm feeling of accomplishment. The number one reason you need a good to-do list is that the human mind is a lousy filing cabinet. It has a million things to think about, and emotions to process, it cannot be relied on to remember to perform the hundreds of administrative tasks you need it to each day. For that, you need a to-do list. In this track, we teach you what a good to-do list task looks like and how to prioritise and separate your tasks and projects. We then look at planning your to-do list and which tools to use. Learning Objectives Learn to manage and prioritize your time more effectively by using to-do lists in the right way Learn the difference between a goal and a task Learn to accomplish more in less time.